A double-blind randomized placebo-controlled study of low dose mirtazapine once daily in patients of major depressive disorders on escitalopram - I., Mallikarjuna Rao; Prayaga, Usha Kiran; Uppada, Dharma Rao; E., Ramachandra Rao; Kudagi, B. L. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The SSRIs being used as 1st line therapy in treatment of depression have delayed therapeutic effect which makes the patient vulnerable to an increased risk of suicide and decreased adherence to the treatment and will prematurely discontinue the therapy. The present study was conducted to evaluate if low dose mirtazapine-escitalopram combination therapy has any add on benefit over monotherapy with escitalopram. Methods: In a single-centered, comparative study involving patients with depression attending the out-patient after screening and exclusion, 60 eligible patients were randomly assigned to receive tablet mirtazapine 7.5 mg plus tablet escitalopram 10 mg intervention or tablet escitalopram 10 mg plus placebo intervention in a double-blind 6-week treatment phase. The primary outcome measure was the change in the 17-item Hamilton Depression Rating Scale (HDRS) and Montgomery-Asberg Depression Rating Scale (MADRS) score from baseline. Participants were evaluated at baseline, 1st, 2nd,4th and 6th week. Results were analyzed using Chi-Square test for adverse effects and independent t-test analysis for efficacy parameter. Results: In the analysis of results at 6th week the numbers of patients achieved remission in mirtazapine group are more with a p-value of 0.018 which is significant and the numbers of responders in mirtazapine group are also more which is statistically significant on chi-square test. There is no significant difference was observed between the two groups with reference to occurrence of adverse effect. Conclusions: Adding low dose mirtazapine has an added benefit in terms of efficacy and getting remission early with more number of responders in the treatment of major depression.